Implementation of Arabic Language Activities to Improve Arabic Language Understanding of MTs Al-Ghozali Jatibarang Indramayu Students - Siti Anisah; Ibnudin (Quality : Journal Of Education, Arabic And Islamic Studies, 2024)
Language is the most basic need for human life, which comes from the holy book and is a reference for Muslims throughout the world. Of the various languages ​​found in the world, Arabic is a language that was born at the beginning of the emergence of language and has been used the longest by humans. That is why this school has issued ideas related to language, one of which is holding Arabic Language activities. Meanwhile, the aim of this research is to find out the implementation of the Arabic language extracurricular in improving the Arabic language of MTs Al-Ghozali students and to be able to find out the influence of the Arabic language extracurricular which is carried out once a week. This type of research can also be called qualitative methods. Carrying out research through interviews with madrasa heads and also students as students as well as documentation and observation. It is hoped that understanding Arabic will make it easier for students to memorize, understand and practice the commands in the Al-Quran in their personal lives.